2016
DOI: 10.1016/j.psychres.2016.04.043
|View full text |Cite
|
Sign up to set email alerts
|

The impact of proposed changes to ICD-11 on estimates of PTSD prevalence and comorbidity

Abstract: The World Health Organization's posttraumatic stress disorder (PTSD) work group has published a proposal for the forthcoming edition of the International Classification of Diseases (ICD-11) that would yield a very different diagnosis relative to DSM-5. This study examined the impact of the proposed ICD-11 changes on PTSD prevalence relative to the ICD-10 and DSM-5 definitions and also evaluated the extent to which these changes would accomplish the stated aim of reducing the comorbidity associated with PTSD. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
55
3
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 45 publications
8
55
3
4
Order By: Relevance
“…In contrast to our assumption and to earlier research (O’Donnell et al, 2014; Stein et al, 2014; Wisco et al, 2016), the provisional PTSD prevalence was increased under the ICD-11 proposal compared to ICD-10. However, the increase was mainly due to the deletion of the time criterion, accounting for a tendency of late symptom onset in the present sample.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to our assumption and to earlier research (O’Donnell et al, 2014; Stein et al, 2014; Wisco et al, 2016), the provisional PTSD prevalence was increased under the ICD-11 proposal compared to ICD-10. However, the increase was mainly due to the deletion of the time criterion, accounting for a tendency of late symptom onset in the present sample.…”
Section: Discussioncontrasting
confidence: 99%
“…However, this population must show a high level of physical and mental fitness, emphasising the need for reliable and valid diagnostic systems and instruments and thus underlining the importance of investigating the concordance and appropriateness of the different diagnostic systems for this trauma population. However, we are aware of only a few studies that examined PTSD prevalence among veterans of war or active soldiers (Gentes et al, 2014; Miller et al, 2013; Morina et al, 2014; Wisco et al, 2016). Although, Gentes et al (2014) and Miller et al (2013) report comparable PTSD prevalence between DSM-IV and DSM-5, and Morina et al (2014) found comparable PTSD prevalence between the ICD-11 proposal and DSM-IV, Wisco et al (2016) report significantly reduced PTSD prevalence under the ICD-11 proposal compared to DSM-5 as well as compared to ICD-10, indicating an unsatisfactory concordance between these systems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Armour, Műllerová, & Elhai, 2015; Colvonen et al, 2017; Kassam-Adams, 2014; Kehle-Forbes & Kimerling, 2017; Molnar et al, 2017; Olff, Van Zuiden, & Bakker, 2015; Wisco et al, 2016). This has led to important discoveries and has inspired some work on improving prevention and intervention strategies for trauma-affected individuals (Brief et al, 2013; Hilton et al, 2017; Horn, Charney, & Feder, 2016; Markowitz et al, 2015; Olff, Armour et al, 2015).…”
Section: Introductionmentioning
confidence: 99%